Reformations compared: religious transformations across early modern Europe - Jefferies, Henry A.; Rex, Richard (Cambridge University Press, 2024)
Reformations Compared presents a collection of comparative studies of the Reformation as it reverberated across Europe in the sixteenth century. Each chapter is focused on two or more comparable geographical spaces, isolating the variables that help explain how and why the Reformation unfolded as it did in each separate setting. Rejecting notions of insularity, the contributors seek out the connections and contrasts that shaped the experience of the Reformation, from the Baltic to the Mediterranean, and from Ireland to Transylvania. In doing so, the volume offers a fresh understanding of the conditions in which the movement succeeded, whether wholly or partially, and those in which it did not. Reformations Compared provides a broad vantage point which encourages readers to reshape their understanding of this decisive episode in European history.